2009
DOI: 10.1177/0363546509331419
|View full text |Cite
|
Sign up to set email alerts
|

Patellofemoral Full-Thickness Chondral Defects Treated With Second-Generation Autologous Chondrocyte Implantation

Abstract: Hyaluronan-based scaffold seeded with autologous chondrocytes can be a viable treatment for patellofemoral chondral lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
157
0
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 193 publications
(176 citation statements)
references
References 38 publications
15
157
0
1
Order By: Relevance
“…The IKDC scores of all our patients were within the 0 to 10th percentile measured on the instrument before surgery. When investigating the use of second-generation ACI in adults for full-thickness patellofemoral chondral defects, Gobbi et al [11] found that in the eight patients who had second-look arthroscopy and biopsies, the repaired surface was nearly normal with biopsy samples characterized as hyaline-like in appearance. Peterson et al [23] studied the durability of autologous chondrocyte transplantation of isolated cartilage defects on the femoral condyle or patella in the adult-aged group and concluded the technique is durable for 5 to 11 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The IKDC scores of all our patients were within the 0 to 10th percentile measured on the instrument before surgery. When investigating the use of second-generation ACI in adults for full-thickness patellofemoral chondral defects, Gobbi et al [11] found that in the eight patients who had second-look arthroscopy and biopsies, the repaired surface was nearly normal with biopsy samples characterized as hyaline-like in appearance. Peterson et al [23] studied the durability of autologous chondrocyte transplantation of isolated cartilage defects on the femoral condyle or patella in the adult-aged group and concluded the technique is durable for 5 to 11 years.…”
Section: Discussionmentioning
confidence: 99%
“…ACI reportedly improves function in patients with full-thickness patellofemoral chondral defects [15]; in one article, chondroplasty increased the level of knee function in 86% of the patients at 2-year followup [14] and in another was associated with durable function for as long as 11 years [23]. Gobbi et al [11] reported improvements in the International Knee Documentation Committee (IKDC) subjective scores (46.09 to 77.06), Tegner-Lysholm (2.56 to 4.94), and EuroQol Visual Analog Scale (56.76 to 78.23) at 2 years using chondrocyte grafts but a decline of the IKDC subjective scores and Tegner-Lysholm scores in patients with multiple and patellar lesions from 2 to 5 years followup. Using arthroscopy, Brittberg et al [5] found transplants were level and had the same macroscopic appearance as the surrounding cartilage at 3 months posttransplant.…”
Section: Introductionmentioning
confidence: 99%
“…The hyaluronic acid-based graft was considered to be ideal for this arthroscopic technique given the physical characteristics, and the clinical success that has been shown when using this scaffold in conjunction with both activated BMAC and ACI. 3,10 The clinical outcomes that have been achieved with the use of HA-BMAC in open cases of cartilage repair have been encouraging, and the arthroscopic technique presented here may be an important step in the advancement of this technology. Medium-to long-term follow-up data from this arthroscopic HA-BMAC procedure will need to be analyzed to confirm restoration of hyaline-like cartilage, and the achievement of successful clinical outcomes similar to that achieved by HA-BMAC implantation performed in an open manner.…”
Section: Discussionmentioning
confidence: 81%
“…Cell-based procedures such as autologous chondrocyte implantation (ACI) have been shown to better stimulate the production of hyaline-like repair tissue, and provide the patient with longer-lasting clinical improvement. 2,3 In addition, ACI in conjunction with a preseeded scaffold has been used arthroscopically, with encouraging success. 4,5 Although the success of marrow stimulation techniques is often related to lesion size and location, cell-based repair procedures have shown good clinical outcomes in cases of large, and even bipolar lesions.…”
mentioning
confidence: 99%
“…Their idea is good as Hyaff-11 has been used clinical in patients for some years with promising results [6,7] but still an osteochondral technique is lacking. The paper is focused on the implantation technique, but the way the authors use the demineralised bone for the support of the Hyaff-11 is interesting.…”
mentioning
confidence: 99%